2023
DOI: 10.3390/ijerph20065053
|View full text |Cite
|
Sign up to set email alerts
|

Male Involvement in Family Planning Decisions in Malawi and Tanzania: What Are the Determinants?

Abstract: The participation of males in joint spousal decisions is urgently needed in achieving the fundamental indicators of reproductive health. The low involvement of males in family planning (FP) decision-making is a major determining factor in low FP usage in Malawi and Tanzania. Despite this, there are inconsistent findings regarding the extent of male involvement and the determinants that aid male participation in FP decisions in these two countries. The objective of this study was to assess the prevalence of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Those husbands who accessed training/education opportunities about reproductive health were 6 times more likely to be involved in their wives SRHRs compared with their counterparts. This finding is supported with study conducted in Myanmar, Nepal and Malawi ( 39 , 40 ). The plausible reason for the association could be the more the husbands have knowledge on SRHRs would have the better involvement.…”
Section: Discussionsupporting
confidence: 87%
“…Those husbands who accessed training/education opportunities about reproductive health were 6 times more likely to be involved in their wives SRHRs compared with their counterparts. This finding is supported with study conducted in Myanmar, Nepal and Malawi ( 39 , 40 ). The plausible reason for the association could be the more the husbands have knowledge on SRHRs would have the better involvement.…”
Section: Discussionsupporting
confidence: 87%
“…Male partners play a fundamental role not just in family planning but in prevention of sexually transmitted infections [ 25 ]. Efforts to involve male partners and provide conducive welcoming hospital environment can promote participation of male partners in family planning [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study align with recent research conducted in Malawi and Tanzania, which reported a prevalence of male involvement in family planning decisions of 53.0% and 26.6%, respectively. 18 This is further supported by a study conducted in Indonesia, which found that the approval of the family planning method by…”
Section: Discussionmentioning
confidence: 78%
“…The findings of this study align with recent research conducted in Malawi and Tanzania, which reported a prevalence of male involvement in family planning decisions of 53.0% and 26.6%, respectively. 18 This is further supported by a study conducted in Indonesia, which found that the approval of the family planning method by spouses positively influenced the uptake of male contraception. 19 This study also revealed decreased willingness for uptake in situations where only male partners were responsible for contraception.…”
Section: Discussionmentioning
confidence: 82%